LIM homeobox protein 5 (Lhx5) is essential for mamillary body development - Miquelajauregui Graf, Amaya; Heide, Michael; Alvarez-Bolado, Gonzalo (Frontiers in neuroanatomy, 2015)
The mamillary body (MM) is a group of hypothalamic nuclei related to memory and spatial navigation that interconnects hippocampal, thalamic, and tegmental regions. Here we demonstrate that Lhx5, a LIM-HD domain transcription factor expressed early in the developing posterior hypothalamus, is required for the generation of the MM and its derived tracts. The MM markers Foxb1, Sim2 and Lhx1 are absent in Lhx5 knock-out mice from early embryonic stages, suggesting abnormal specification of this region. This was supported by the absence of Nkx2.1 and expansion of Shh in the prospective mamillary area. Interestingly, we also found an ectopic domain expressing Lhx2 and Lhx9 along the anterio-posterior hypothalamic axis. Our results suggest that Lhx5 controls early aspects of hypothalamic development by regulating gene expression and cellular specification in the prospective MM.
Gesehen am 08.06.2020